Potential Use of Contrast-Enhanced Ultrasound (CEUS) in the Detection of Metastatic Superficial Lymph Nodes in Melanoma Patients - Rubaltelli, L.; Beltrame, V.; Scagliori, E.; Bezzon, E.; Frigo, A. C.; Rastrelli, M.; Stramare, R. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: Malignant melanoma represents a significant and growing public health burden worldwide. Ultrasonography is the most useful diagnostic modality for regional lymph nodal staging. Because any focal areas of cortical lobulation or thickening-swelling should also be considered as a sign of metastases, we are going to report the usefulness of contrast-enhanced ultrasonography (CEUS) in the differential diagnosis of benign or malignant lymph nodes in patients with malignant melanoma based on blood stream patterns and investigate the diagnostic capability.Patients and Methods: After the excision of cutaneous melanoma with positive excision margins but with negative sentinel lymph node, 540 patients underwent US of superficial lymph nodes. The inclusion criteria for CEUS consisted of both major signs (absence of the echogenic hilus, round shape, and peripheral capsular vascularity) and minor ones (the presence of focal cortical thickening). The diagnostic capability was evaluated by comparing the cytological findings with the enhancement pattern on CEUS. Results: US in combination with CEUS correctly classified 534/540 patients. CEUS applied to lymph nodes with focal cortical thickening on grayscale US confirmed great sensitivity (0.98) and specificity (0.99) but above all, it showed a markedly improved accuracy of 0.99. The likelihood ratios confirmed the good performance of the methods used.Conclusion: CEUS increases the diagnostic accuracy of US in the differential diagnosis of benign and malignant LNs but it also allows us, when possible, to avoid unnecessary invasive operations such as LN FNAC. Moreover, CEUS may guide FNAC in the case of focal cortical thickening on the basis of hypoperfusion, with a reduction in the number of false negatives and much earlier detection of nodal metastatic foci.
Keywords: lymphatic; melanoma; metastases; microbubbles; ultrasound